2018
DOI: 10.18502/ken.v3i2.1817
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of Bare Nanoparticles Based on Silicon and Gold for Nervous Cells

Abstract: This work aimed to investigate the biocompatibility of bare (ligand-free) lasersynthesized nanoparticles (NPs) based on silicon (Si) and gold (Au) with primary hippocampal cultures. 1%, 5% and 7% of culture medium were replaced by 0.1 mg/mL NP solution on day 14 of culture development in vitro. Our studies revealed that the NPs caused a dose-dependent cytotoxic effect, which was manifested by an increase the number of dead cells and a decrease of the spontaneous functional calcium activity of neural networks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Suh et al demonstrated that TiO 2 nanoparticles tends to be less hazardous to organisms than silica [44]. Mishchenko et al [45] studied the biocompatibility of Si and Au nanoparticles with primary hippocampal cultures. Dose dependent cytotoxic effect was found for both Si and Au nanoparticles but Au nanoparticles exhibited less pronounced cytotoxic effects [45].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suh et al demonstrated that TiO 2 nanoparticles tends to be less hazardous to organisms than silica [44]. Mishchenko et al [45] studied the biocompatibility of Si and Au nanoparticles with primary hippocampal cultures. Dose dependent cytotoxic effect was found for both Si and Au nanoparticles but Au nanoparticles exhibited less pronounced cytotoxic effects [45].…”
Section: Introductionmentioning
confidence: 99%
“…Mishchenko et al [45] studied the biocompatibility of Si and Au nanoparticles with primary hippocampal cultures. Dose dependent cytotoxic effect was found for both Si and Au nanoparticles but Au nanoparticles exhibited less pronounced cytotoxic effects [45]. It should be acknowledged that Si based nanomaterials may not be the best choice for biomedical applications considering biocompatibility and safety.…”
Section: Introductionmentioning
confidence: 99%